2011
DOI: 10.1002/fuce.201000176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Contact between Electrode and Interconnect on Performance of SOFC Stacks

Abstract: This work investigates the effect of contact between electrodes and alloy interconnects on output performance of solid oxide fuel cell (SOFC) stacks. The measured maximum output power density (pmax) of the unit cell increases from 0.07 to 0.1 W cm–2 by increasing the tip area of the interconnect from 40 to 60 cm2. The pmax increases from 0.07 to 0.15 W cm–2 upon the addition of nickel foam and Ag mesh on the anode and cathode side, respectively. An additional (La0.75Sr0.25)0.95MO3–σ cathode current collecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…[11][12][13] Furthermore, the quantitative contributions of the resistance sources of components to stack performance were obtained by our group. We concluded that stack performance is signifi cantly affected by cell performance itself when excellent stack sealing and contact among internal components are provided.…”
mentioning
confidence: 99%
“…[11][12][13] Furthermore, the quantitative contributions of the resistance sources of components to stack performance were obtained by our group. We concluded that stack performance is signifi cantly affected by cell performance itself when excellent stack sealing and contact among internal components are provided.…”
mentioning
confidence: 99%
“…2b) and c) shows that the boundaries of cathode contact for cells #1 and 2 can be clearly distinguished. Based on our previous results [17], the difference in power density between repeating units 1 and 2 is mainly due to the difference in electron transfer resistance at the cathode side. .…”
Section: Resultsmentioning
confidence: 76%
“…For instance, new electrode materials [5][6][7][8] and nanostructures [9][10][11] have been reported, which resulted in a maximum power density ≥ 2.9 W•cm −2 at 650 o C with humidified 3% H 2 as fuel and air as oxidant. On the contrary, the power density of an SOFC stack is generally less than 0.6 Wcm −2 [12][13][14][15], which determined by the contact layer between the cathode and the interconnect [16][17][18][19][20]. Because of the high-temperature oxidation atmosphere at the cathode side, researchers initially attempted to print noble metal slurry on the cathode as a current collector [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The single cell active area is 70cm 2 . The detailed parameters of cells can be seen elsewhere (11)(12)(13). The Fe-16Cr alloy was used Figure 4 shows the result of a 2-cell stack working under SOEC and SOFC mode alternately.…”
Section: Durability Of High Temperature Seam Electrolysis For Hydrogementioning
confidence: 99%